Phenology and phyllochron of seven strawberry cultivars grown in substrate and greenhouse in the Brazilian subtropics - Deggerone, Yuri dos Santos; Trentin, Thomas dos Santos; Kujawa, Sabrina Carla; Albrecht, Gustavo Eduardo; Fante, Rudinei; Kaspary, Ivan Junior; Fornari, Michele; Chiomento, José Luís Trevizan (Comunicata Scientiae, 2023)
Knowing the phenology and phyllochron of strawberry cultivars allows the establishment of phytotechnical managements aimed at enhancing the productive chain of this horticultural crop. Thus, the objective of this work was to investigate whether phenology and phyllochron differ among strawberry cultivars grown in substrate and greenhouse. The treatments were seven strawberry cultivars arranged in a randomized block design, with four replications. Leaf emission rate, occurrence and duration of phenological stages were evaluated. ‘Fronteras’ was considered the earliest to start fruiting, as it had the lowest phyllochron value, while ‘Albion’ was the latest. Through multivariate analysis, the formation of two groups among strawberry cultivars was observed according to their phenological characteristics. Group 1 gathered the five strawberry cultivars classified as having neutral-days in terms of flowering and group 2 was composed of the two short-day cultivars. It is concluded that, under the cultivation conditions of southern Brazil, ‘Fronteras’ is the earliest to start the fruit harvest, provided it is transplanted in May, and ‘Albion’ is the latest. Neutral-day cultivars have a shorter transplant cycle until the beginning of harvest, while short-day cultivars require a longer interval for this transition, with a prolonged vegetative period.